2016
DOI: 10.1074/jbc.m116.741561
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Violacein, Structure and Function of l-Tryptophan Oxidase VioA from Chromobacterium violaceum

Abstract: Violacein is a natural purple pigment of Chromobacterium violaceum with potential medical applications as antimicrobial, antiviral, and anticancer drugs. The initial step of violacein biosynthesis is the oxidative conversion of L-tryptophan into the corresponding ␣-imine catalyzed by the flavoenzyme L-tryptophan oxidase (VioA). A substrate-related (3-(1H-indol-3-yl)-2-methylpropanoic acid) and a product-related (2-(1H-indol-3-ylmethyl)prop-2-enoic acid) competitive VioA inhibitor was synthesized for subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 67 publications
(83 reference statements)
4
50
2
1
Order By: Relevance
“…Multiple sequence alignment of 14 VioA homologues from various bisindole pathways that were characterized previously, shows that while Arg64 and Tyr309 are conserved among the VioA homologues, His163 is replaced by Asn in HysO and AbeO ( Figure S7), supporting the hypothesis that His163 is not required for catalytic activity of VioA in a previous study 14 . It would be interesting to compare the reaction kinetics of VioA homologues from other bisindole pathways, such as StaO (staurosporine pathway) 23 , EspO (erdasporine pathway) 37 and HysO …”
Section: Purification Of 7-chloro Analogues Of Violacein and Deoxyviosupporting
confidence: 82%
See 4 more Smart Citations
“…Multiple sequence alignment of 14 VioA homologues from various bisindole pathways that were characterized previously, shows that while Arg64 and Tyr309 are conserved among the VioA homologues, His163 is replaced by Asn in HysO and AbeO ( Figure S7), supporting the hypothesis that His163 is not required for catalytic activity of VioA in a previous study 14 . It would be interesting to compare the reaction kinetics of VioA homologues from other bisindole pathways, such as StaO (staurosporine pathway) 23 , EspO (erdasporine pathway) 37 and HysO …”
Section: Purification Of 7-chloro Analogues Of Violacein and Deoxyviosupporting
confidence: 82%
“…At the substrate-FAD interface, two key residues, Arg64 and Tyr309, were close to the charged carboxylate group of the substrate, positioning the Cα atom next to the FAD isoalloxazine plane ( Figure 4B). However, a previous study found that while Arg64 and Tyr309 are essential for catalytic activity, His163 is unnecessary as a VioA H163A mutant retained 85% of WT activity, suggesting that the hydride transfer from Cα and amine groups of Ltryptophan may not require acid-base catalysis of the H163 side chain 14 .…”
Section: Purification Of 7-chloro Analogues Of Violacein and Deoxyviomentioning
confidence: 91%
See 3 more Smart Citations